Open access’ dan wacana pengembangan perpustakaan akademik berkelanjutan - Agus Rifai (Pusat Perpustakaan UIN Syarif Hidayatullah Jakarta, 2017)
This paper deals with the concept of open acces in academic libraries, and in relation on the sustainable academic library development discourses. Based on literature review, it was found that open acces play strategic roles in the development of sustainable academic library. It i provides oppotunities and challanges as we ll as needs for academic libraries to re-orientate the r paradigm in providing acces and services to information. Open acces offers a wider acces to information as the implementation of “openes of information” and “ library for all” principles. It also provides a foundation for the sustainability of academic libraries and for universi-ty scholarship development